Visible-Light-Induced Intermolecular Atom-Transfer Radical Addition of Benzyl Halides to Olefins: Facile Synthesis of Tetrahydroquinolines - Paria, Suva; Pirtsch, Michael; Kais, Viktor; Reiser, Oliver (Synthesis, 2013)
Cu(dap)2Cl has been utilized as a visible-light photoredox catalyst for the atom-transfer radical addition (ATRA) of benzyl halides to styrenes and silyl enol ethers. The resulting ATRA products can be readily converted into tetrahydroquinolines.
Keywords: visible-light photocatalysis; atom-transfer radical addition; benzyl halide; tetrahydroquinoline